Research on population quantity of main amphibian in Zhejiang province - TAO Ji-xing; LIU An-xing; SUN Meng-jun (浙江大学学报. 农业与生命科学版, 2004)
By means of systematical sampling and belts sampling, and mark release recapture, a research on the quantity of population of predominant amphibians in Zhejiang Province was conducted. According to the investigation and calculation, the distribution range, appearance density and population quantity of 7 amphibians may be summarged as below: Bufob. gargarizans is distributed over the whole Zhejiang, 32.06 ind./km2 and 326.37×104 individuals totally; B. melanostictus is distributed over the south of Zhejiang, 9.68 ind./km2 and 28.50×104 individuals; Rana guentheri is distributed over the south of Zhejiang, 36.25 ind./km2 and 106.75×104 individuals; R. nigromaculata is distributed over the whole Zhejiang, 121.61 ind./km2 and 1237.99×104 individuals; R. spinosa is distributed over the continent of Zhejiang, 4.35 ind./km2 and 43.44×104 individuals; R. tigrina rugulosa is distributed over the whole Zhejiang, 5.40 ind./km2 and 54.97×104 individuals; Echinotriton chinhaiensis is distributed only over Beilun District of Ningbo City, 9.87 ind./km2 and 592 individuals. The authors further give an appraisal on the population resources of amphibians in Zhejiang.